2020
DOI: 10.12659/msm.926763
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Infection Reduces Kynurenic Acid Production and Reverses Th17/Treg Balance by Modulating Indoleamine 2,3-Dioxygenase (IDO) Molecules in Plasmacytoid Dendritic Cells

Abstract: Background Respiratory syncytial virus (RSV) infection causes a world-wide medical and economic burden. This study analyzed the effects of RSV infection on plasmacytoid dendritic cells (pDCs) and evaluated the immunopathogenesis of RSV infection by measuring relative numbers of FoxP3+ Treg cells and Th17 cells. Material/Methods pDCs were isolated from human blood samples, purified using magnetic microbeads, and treated with RSV, IFN-γ, or vehicle. These cells were mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…A lower Th1 response to RSV might hinder viral clearance and probably promote the development of allergic diseases ( 43 ). Jin et al showed that RSV infection reduced kynurenic acid production and inhibited the transformation from Th17 to Foxp3 + regulatory T cells (Tregs) (Th17/Treg balance) by altering IDO activity in plasmacytoid DCs (pDCs) ( 44 ), which might disrupt asthma tolerance later in life ( 45 ). High expression of IDO1 in bat neutrophils was observed in a single-cell transcriptome analysis study of viral infection response in bats, which may play an important role in limiting inflammation in the context of neutrophil-activated conditions ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…A lower Th1 response to RSV might hinder viral clearance and probably promote the development of allergic diseases ( 43 ). Jin et al showed that RSV infection reduced kynurenic acid production and inhibited the transformation from Th17 to Foxp3 + regulatory T cells (Tregs) (Th17/Treg balance) by altering IDO activity in plasmacytoid DCs (pDCs) ( 44 ), which might disrupt asthma tolerance later in life ( 45 ). High expression of IDO1 in bat neutrophils was observed in a single-cell transcriptome analysis study of viral infection response in bats, which may play an important role in limiting inflammation in the context of neutrophil-activated conditions ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data clearly show that IDO deficiency provides markedly enhanced Th17- and Th1-type airway inflammation in the course of hRV-induced asthma exacerbation. It has been reported that infections with respiratory viruses such as RSV and influenza induce IDO expression ( 36 37 ), but no previous study had used practical models infected by a major cause of asthma exacerbation to examine the role of IDO in asthma exacerbation. The IDO-ablated mice displayed Th17- and Th1-type airway inflammation, as manifested by large increases in neutrophil infiltration, enhanced airway responsiveness, and increased production of Th17- and Th1-type cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory viral infection can affect IDO expression and thereby alter asthmatic airway inflammation. Respiratory syncytial virus (RSV), another important cause of asthma exacerbation, induces the expression and bioactivity of IDO in human DCs derived from monocytes, which suggests that IDO has a potentially novel role in the development of asthma exacerbation ( 36 ). In contrast, RSV reduces KYN production and reverses the Th17/Treg balance by modulating IDO expression in pDCs ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely important in RSV vaccine development. In mice, RSV infection of pDCs that are co-cultured with T cells has reduced the transformation of Th17 cells to FoxP3 + Tregs [172]. Similarly in mice, RSV infection of DCs impairs T cell activation by affecting synapse assembly [173].…”
Section: Dendritic Cellsmentioning
confidence: 99%